2015
DOI: 10.3390/nu7075111
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting 25-Hydroxyvitamin D Concentration in Response to Vitamin D Supplementation

Abstract: Sun exposure is the main source of vitamin D. Due to many lifestyle risk factors vitamin D deficiency/insufficiency is becoming a worldwide health problem. Low 25(OH)D concentration is associated with adverse musculoskeletal and non-musculoskeletal health outcomes. Vitamin D supplementation is currently the best approach to treat deficiency and to maintain adequacy. In response to a given dose of vitamin D, the effect on 25(OH)D concentration differs between individuals, and it is imperative that factors affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
141
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 102 publications
(212 reference statements)
9
141
6
2
Order By: Relevance
“…We may have seen this result because our sample size was very large and we could adjust for many potential confounders. Our results also contrast with studies that reported a significant association between response to supplementation and BMI (27), including a systematic review suggesting that the dose per kilogram of body weight explains 34.5% of the serum response (28). Although BMI affected baseline serum 25(OH)D concentrations, it did not independently affect the serum response to supplementation in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We may have seen this result because our sample size was very large and we could adjust for many potential confounders. Our results also contrast with studies that reported a significant association between response to supplementation and BMI (27), including a systematic review suggesting that the dose per kilogram of body weight explains 34.5% of the serum response (28). Although BMI affected baseline serum 25(OH)D concentrations, it did not independently affect the serum response to supplementation in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although BMI affected baseline serum 25(OH)D concentrations, it did not independently affect the serum response to supplementation in our study. Other studies provide mixed or limited evidence that response to supplementation is associated with calcium intake, estrogen use, and dietary fat (27), but our results supported none of these associations. The inconsistencies seen across studies may reflect small sample sizes, as well as differences in the covariates collected and how they were measured.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations